El Excentrico, 1979-01-20 - Garcia, Bert:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2024)
January 20, 1979 [20 de enero de 1979]. Ano 29, No 20. Cover contains a photo of guiraist Ricardo Peti. He would be performing at the San Jose City Colllege Theater on February 17th, 1979.